ANALISIS PENGARUH PASANG SURUT TERHADAP EFEKTIVITAS OPERASI PINTU AIR DI SUNGAI PETUNG PASURUAN - Djaelani, Mohamad; Priambodo, Sebastianus (Fakultas Teknik Universitas Palangka Raya, 2026)
This study aims to assess the influence of tidal fluctuations on the operational effectiveness of a sluice gate in the Petung River, Pasuruan. A quantitative approach was employed, combining hydrological analysis, tidal analysis, and hydraulic modeling using HEC-RAS under unsteady flow conditions. The dataset includes rainfall records, river discharge obtained from AWLR, and tidal data applied as the downstream boundary condition. Dependable discharge was determined using Q80% and Q95% probabilities, while tidal characteristics were analyzed to describe water level variability. The results indicate that the dependable discharge ranges from 0.548–0.730 m³/s (Q80%) and 0.416–0.526 m³/s (Q95%), reflecting limited flow during dry conditions. Tidal variation shows a considerable range, with maximum water levels reaching 2.80 m and minimum levels around 0.41 m, significantly affecting the river water profile. Hydraulic simulation reveals the occurrence of a backwater effect during high tide, leading to upstream water level rise and reduced flow capacity. The evaluation further indicates that sluice gate performance decreases during high tide due to downstream pressure, while flow conditions improve during low tide. Therefore, an adaptive operation strategy based on tidal patterns is required to enhance flow regulation and minimize flood risk.